Opportunistic relaying with analogue and digital network coding for two‐way parallel relay network. Issue 12 (1st August 2014) - Dai, Mingjun; Wang, Hui; Lin, Xiaohui; Zhang, Shengli; Chen, Bin
Abstract : A pair of terminals exchanging information via a layer of parallel relay nodes under slow fading is considered. Two protocols are proposed based on the combination of opportunistic relaying (OR) with analogue network coding (ANC), named ORANC, or with digital network coding (DNC), named ORDNC, respectively. Two schemes/versions of ORDNC, including 2‐phase ORDNC (2P‐ORDNC) and 3‐phase ORDNC (3P‐ORDNC) are proposed. Their outage performances are investigated. ORANC and 2P‐ORDNC are proved to achieve optimal diversity‐multiplexing tradeoff (DMT), whereas 3P‐ORDNC is proved to be suboptimal. However, from diversity viewpoint only, all the above schemes are proven to achieve full diversity order. Simulation results verify the analysis, and show that 3P‐ORDNC and ORANC shows advantage at low‐ and high‐data rate regions, respectively.